Estimating the Impact of the Balassa-Samuelson Effect in Central and Eastern European Countries: A Revised Analysis of Panel Data Cointegration Tests - Miletić, Mirjana (Panoeconomicus, 2012)
This paper aims to reassess the contribution of the Balassa-Samuelson effect to the inflation and real exchange rate appreciation using panel data for nine CEECs covering the period ranging from the mid-1990s to the third quarter of 2010. The main idea of this analysis is to answer the question of whether the Global Economic Crisis had a significant impact on the efforts of CEECs to stay on the path of real convergence. The Balassa-Samuelson effect explains less than 1.5 percentage points on average of inflation differential relative to the euro area and around 1 percentage point of the total domestic inflation. The results are robust across the model specification and estimation method. Most of the results point out that the Balassa-Samuelson effect has not changed considerably during the crisis even though it is lower compared to that in the earlier stage of transition (for the period up to 2004). Key words: Baumol-Bowen effect, Balassa-Samuelson effect, Real appreciation, Inflation. JEL: C52, E01, O11.